Extracorporeal membrane oxygenation in transcatheter aortic valve replacement. (January 2017) - Dolmatova, Elena; Moazzami, Kasra; Cocke, Thomas P; Elmann, Elie; Vaidya, Pranay; Ng, Arthur F; Satya, Kumar; Narayan, Rajeev L
Background: Patients undergoing transcatheter aortic valve replacement can experience severe perioperative complications leading to hemodynamic instability and death. Venoarterial extracorporeal membrane oxygenation can be used to provide cardiorespiratory support during this time. Methods: From 2012 to 2015, of 247 patients who underwent transcatheter aortic valve replacement, 6 (2.42%) required extracorporeal membrane oxygenation support. Their mean age was 82 ± 7.4 years, mean Society of Thoracic Surgeons score was 9.4 ± 6.6, and mean aortic gradient was 28.3 ± 12 mm Hg. Rescue extracorporeal membrane oxygenation was required for hemodynamic instability due to ventricular fibrillation ( n = 1), respiratory failure ( n = 1), left ventricular wall rupture ( n = 2), and aortic annulus rupture ( n = 1). In one patient, prophylactic extracorporeal membrane oxygenation was required due to advanced heart failure. Additional procedures included valve-in-valve implantation ( n = 1), conversion to an open procedure ( n = 3), and intraaortic balloon pump insertion ( n = 1). Results: The median hospital stay was 20 days. There were 2 hospital deaths in patients whose hospital course was complicated by left ventricular wall rupture or aortic annulus rupture with resulting tamponade. Among the 4 survivors, one required continuous ventilator support following discharge, and 3 experienced no major complications during the first month after discharge. Conclusions: Extracorporeal membrane oxygenation can be considered a viable option for high-risk patients undergoing transcatheter aortic valve replacement and those who develop cardiac complications following this procedure and require cardiorespiratory support.